2015
DOI: 10.1371/journal.pone.0123618
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Response Factors Are Controlled by Multiple Harvesting Stresses in Hevea brasiliensis

Abstract: Tolerance of recurrent mechanical wounding and exogenous ethylene is a feature of the rubber tree. Latex harvesting involves tapping of the tree bark and ethephon is applied to increase latex flow. Ethylene is an essential element in controlling latex production. The ethylene signalling pathway leads to the activation of Ethylene Response Factor (ERF) transcription factors. This family has been identified in Hevea brasiliensis. This study set out to understand the regulation of ERF genes during latex harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 44 publications
3
39
2
8
Order By: Relevance
“…Ethylene treatment triggers a number of stimulated downstream biochemical cascades in relation to latex production: sugar loading and its catabolism 9,36,39,40 , water uptake 41 , energy availability 42 , cytosolic alkalinization 42 , nitrogen assimilation 43 and defence responses 44 . Many genes implicated in these events were among the DEGs identified in this study (Supplementary Tables 22 and 23), but not the rubber biosynthesis genes, which is consistent with the previous proposition that ethylene has little direct effect on genes in rubber biosynthesis 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Ethylene treatment triggers a number of stimulated downstream biochemical cascades in relation to latex production: sugar loading and its catabolism 9,36,39,40 , water uptake 41 , energy availability 42 , cytosolic alkalinization 42 , nitrogen assimilation 43 and defence responses 44 . Many genes implicated in these events were among the DEGs identified in this study (Supplementary Tables 22 and 23), but not the rubber biosynthesis genes, which is consistent with the previous proposition that ethylene has little direct effect on genes in rubber biosynthesis 45 .…”
Section: Resultsmentioning
confidence: 99%
“…However, these GEMs may or may not have all important function in rubber tree. Putranto et al (2015b) and Putranto et al (2015a) In general results, high relative abundance of transcripts were detected in several groups of HbAP2/ERFs 2015a;2015b). Although some members of these groups have not proven to be GEMs, high level of expression leads us to suggest their involvement in some regulation at the molecular level.…”
Section: Identification Of Ap2/erf Gene Expression Markers Related Wimentioning
confidence: 88%
“…In parallel with the work of Piyatrakul, the characterization of Hevea AP2/ERF superfamily was similarly addressed by studying their stress response as well as during the occurrence of tapping panel dryness (Table 1) (Putranto et al, 2015b, Putranto et al, 2015a was identified using high-debit qPCR analysis from the juvenile plant samples which were generated from the somatic embryogenesis prepared in CIRAD (Putranto et al, 2015a).…”
Section: Characterization Of the Ethylene Biosynthesis And Signallingmentioning
confidence: 99%
See 2 more Smart Citations